2018
DOI: 10.3390/ijms19113350
|View full text |Cite
|
Sign up to set email alerts
|

Oleandrin and Its Derivative Odoroside A, Both Cardiac Glycosides, Exhibit Anticancer Effects by Inhibiting Invasion via Suppressing the STAT-3 Signaling Pathway

Abstract: The cardiac glycosides oleandrin and odoroside A, polyphenolic monomer compounds extracted from Nerium oleander, have been found to have antitumor effects on various tumors at low doses. However, the mechanisms of anticancer effects of oleandrin and odoroside A are not well known. Therefore, in this study, we aimed to investigate the anticancer effects of oleandrin and odoroside A and their associated mechanisms in highly metastatic MDA-MB-231 breast cancer cells and radiotherapy-resistant (RT-R) MDA-MB-231 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 59 publications
2
18
0
4
Order By: Relevance
“…Added to that, these authors also showed that MMP-9 expression correlates with that of activated Stat3 in human breast cancer specimens. This is in accordance with other recent report showing that inhibition of STAT-3 abolishes the activity of MMP-9 in MDA-MB-231 cells (40). Finally, Knock down of STAT3 in the multidrug resistant breast cancer, SK-BR-3/EPR, cell line inhibited cell invasion and downregulated MMP-9 in these cells (41).…”
Section: Discussionsupporting
confidence: 94%
“…Added to that, these authors also showed that MMP-9 expression correlates with that of activated Stat3 in human breast cancer specimens. This is in accordance with other recent report showing that inhibition of STAT-3 abolishes the activity of MMP-9 in MDA-MB-231 cells (40). Finally, Knock down of STAT3 in the multidrug resistant breast cancer, SK-BR-3/EPR, cell line inhibited cell invasion and downregulated MMP-9 in these cells (41).…”
Section: Discussionsupporting
confidence: 94%
“…Knowledge of the pharmacology of cardiac glycosides such as oleandrin derived exclusively from Nerium oleander , however, has expanded greatly over the last 20 years ( Newman et al., 2008 ; Riganti et al., 2011 ). For example, proposed anti-proliferative mechanisms of oleandrin have included reports of altered membrane fluidity ( Manna et al., 2006 ), decreased activation of Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-κB), c-Jun N-terminal kinase (JNK) and activator protein 1 (AP-1) ( Manna et al., 2000 ), increased cellular calcium ( McConkey et al., 2000 ), inhibition of the Signal transducer and activator of transcription 3 (STAT-3) signaling pathway ( Ko et al., 2018 ), decreased phosphorylation of Protein kinase B (Akt) ( Afaq et al., 2004 ), decreased cellular transport of basic fibroblast growth factor 2 (FGF-2) ( Smith et al., 2001 ), initiation of Apo2 ligand/tumor necrosis factor (TNF)-related apoptosis-inducing ligand (Apo2L/TRAIL) apoptosis via increased expression of death receptors 4 and 5 ( Frese et al., 2006 ), induction of immunogenic cell death ( Menger et al., 2012 ; Diederich et al., 2017 ), and inhibition of components of the mammalian target of rapamycin (mTOR) pathway ( Schoner and Scheiner-Bobis, 2007 ) to name but a few. In addition, our research and that of others have shown a strong ability of oleandrin to induce the synthesis of brain derived neurotrophic factor (BDNF), which may be essential to augmentation of normal brain health ( Van Kanegan et al., 2014 ; Garofalo et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from being a cardiac glycoside, oleandrin has been gathering attention due to its anti-tumoral [ 12 , 13 , 14 , 15 , 16 ] and antiviral potential [ 8 , 17 , 18 , 19 ], but its pharmacological use is held back by its variable toxicity. In this study, using the model S. cerevisiae , we detected oleandrin-induced fluctuations in cell Ca 2+ , which could be related to the Ca 2+ entry via the Cch1/Mid1 plasma membrane channel ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%